2020
DOI: 10.1128/msphere.00060-20
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Hospital-Based Prospective Surveillance Study of Bacterial Agents Causing Meningitis and Seroprevalence of Different Serogroups of Neisseria meningitidis, Haemophilus influenzae Type b, and Streptococcus pneumoniae during 2015 to 2018 in Turkey

Abstract: The etiology of bacterial meningitis in Turkey changed after the implementation of conjugated vaccines against Streptococcus pneumoniae and Haemophilus influenzae type b (Hib) in the Turkish National Immunization Program (NIP). Administration of Hib vaccine and PCV-7 (7-valent pneumococcal conjugate vaccine) was implemented in NIP in 2006 and 2009, respectively. In 2011, PCV-7 was replaced with PCV-13. Meningococcal vaccines have not yet been included in Turkish NIP. This prospective study comprised 27 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…Within the etiological agents of virusassociated encephalitis, we found influenza as the most common causative agent, indicating a resemblance to the study from Japan. In our study, the most common etiology of acute bacterial meningitis was Neisseria meningitides, similar to a multicenter surveillance study from Turkey that reported the same organism as the most frequently encountered cause of acute bacterial meningitis in children [28]. It is interesting that various unusual pathological agents were identified in the study, including Rabies virus, Clostridium tetani and Hydatid cyst.…”
Section: Discussionsupporting
confidence: 87%
“…Within the etiological agents of virusassociated encephalitis, we found influenza as the most common causative agent, indicating a resemblance to the study from Japan. In our study, the most common etiology of acute bacterial meningitis was Neisseria meningitides, similar to a multicenter surveillance study from Turkey that reported the same organism as the most frequently encountered cause of acute bacterial meningitis in children [28]. It is interesting that various unusual pathological agents were identified in the study, including Rabies virus, Clostridium tetani and Hydatid cyst.…”
Section: Discussionsupporting
confidence: 87%
“…Hib meningitis incidence declined by 72–83% at sentinel hospitals in Pakistan and Bangladesh, respectively, within two years of implementing nationwide Hib conjugate vaccination [ 80 ]. In a hospital-based multi-center prospective survey of bacterial meningitis in Turkey from 2015 to 2018, 994 cases of suspected bacterial meningitis in children, aged one month to 18 years, were identified [ 81 ]. Three (2.4%) of the 125 culture-positive cases were caused by Hib.…”
Section: Impact Of Hib Conjugate Vaccine On Hib Meningitismentioning
confidence: 99%
“…A drastic change in the aetiology of childhood meningoencephalitis has occurred in Turkey since vaccination programmes have eradicated mumps, measles and rubella associated encephalitides. There is no study involving the national incidence rates of viral meningoencephalitis, except for Ceyhan et al’s studies that have been following bacterial meningitis surveillance nationally for years 5 . We identifed a considerable number of associated agents, nine different viruses in 50 of 186 cases.…”
Section: Discussionmentioning
confidence: 99%